Evaluation of Cuspal Deflection in Mesioocclosodistal Restorations Using Universal Adhesive and Bulkfill Composite - Maryam Shakur Shahabi; Atefeh Yousefi Jordehi; Behzad Hamzehei (Mashhad University of Medical Sciences, 2019)
Introduction: Bulkfill composites and universal adhesives were introduced to reduce the stages and sensitivity of composite restorations. The current study aimed to identify cuspal deflection in mesioocclosodistal (MOD) restorations using universal adhesives and bulk-fill composite. Materials and Methods: A number of 58 newly extracted upper premolars were assigned to four groups and then restored using bulky and incremental techniques with Filtek Bulkfill composite and G-Premio and Adper Single Bond adhesives. Firstly, each tooth was prepared for a standardized MOD cavity where the width of the proximal box was two-thirds the bucolingual width, the occlusal isthmus half the bucolingual width with the cavity depth at the occlusal isthmus standardized to 3.5 mm - from the tip of the palatal cusp and 1 mm above the CEJ at the cervical aspect of the proximal boxes.  Before and after restoring, the intercuspal distance of each tooth was measured by digital micrometer at 0, 30, 60 and 180 seconds after light curing.  The average values were calculated and the amount of cuspal deflection obtained by subtracting the number acquired after the restoration from the number prior to restoration. The obtained data were analyzed in the related software using one-way ANOVA due to the normality of results. A P-value less than 0.05 was considered statistically significant. Results: As evidenced by the obtained results, significant difference existed in cuspal deflection values among studied groups. Using pairwise Tukey's test, a significant difference was observed between the restored group using bulky technique with the application of G-Premio adhesive and the group that applied G-Premio adhesive using the incremental technique. Conclusion: Based on the results of the current study, clinical chair time can be reduced by the bulky application of bulkfill composite along with total etch and universal adhesives.